Multi-Signal Induction Motor Broken Rotor Bar Detection Based on Merged Convolutional Neural Network - Tianyi Wang; Shiguang Wen; Shaotong Sheng; Huimin Ma (Actuators)
Motor fault detection plays a vital role in industrial maintenance. Timely detection of faults in their early stages can prevent catastrophic consequences and reduce maintenance costs. Traditional methods face challenges in motor broken rotor bar (BRB) detection: model-driven methods are difficult to apply accurately in complex and changing environments, while data-driven methods usually require sophisticated feature extraction and classification processes. In this paper, we propose a novel non-invasive fault detection method. The method preprocesses motor currents by Hilbert-Huang Transform (HHT) and Park’s Vector Modulus (PVM) and then uses a merged convolutional neural network (CNN) for classification. This experiment investigates the detection of broken rotor bars of motors with different loads (25%, 50%, 75%, and 100% of rated load) and different fault levels (Normal, 1BRB, 2BRB, 3BRB, and 4BRB). The results show that the model’s classification accuracy exceeds 95% under various operating conditions and can maintain high accuracy under low load conditions, thus addressing the limitations faced by existing methods. In addition, it is computationally efficient and can guarantee high real-time performance. This method combines advanced signal processing techniques and deep learning algorithms to provide a practical solution for motor broken rotor bar detection.